GM‐CSF as successful salvage therapy of metamizole (dipyrone)‐induced agranulocytosis with Fournier's gangrene and severe septic shock in an adolescent. Issue 8 (20th July 2016) - Winkler, Annegret; Kietz, Silke; Bahlmann, Hagen; Jafarzade, Gunel; Lode, Holger N.; Heckmann, Matthias
Key Clinical Message: This case report describes the successful use of granulocyte and macrophage colony‐stimulating factor as salvage therapy and an alternative to hematopoietic stem cell transplantation in a 14‐year‐old adolescent with metamizole (dipyrone)‐induced agranulocytosis and severe septic shock. Abstract : This case report describes the successful use of granulocyte and macrophage colony‐stimulating factor as salvage therapy and an alternative to hematopoietic stem cell transplantation in a 14‐year‐old adolescent with metamizole (dipyrone)‐induced agranulocytosis and severe septic shock.